Effect of Adaptive Teaching Strategy on Students’ Academic Achievement and Interest in Biology in Tudun Wada Educational Zone, Kano State, Nigeria - Mubarak , Saidu; Mamuda , Sani Salisu; Bello, Saudat S.; Ahmad, Insaf; Nuhu , Buhari Idris; Abdulhalim , Bashir Sulaiman; Dahiru , Auwalu Musa (Kashere Journal of Education, 2025)
This study investigated the effect of an adaptive teaching strategy on senior secondary school students’ academic achievement and interest in biology in the Tudun Wada Educational Zone, Kano State, Nigeria. The study objectives are to determine the effect of an adaptive teaching strategy on students’ academic achievement in Biology, examine its effect on students’ interest in Biology, and determine whether gender influences students’ academic achievement when taught using this strategy. A quasi-experimental pretest–posttest control group design was employed. The population comprised 1,114 SS II Biology students from 16 public secondary schools. A sample of 259 students was chosen using stratified and simple random sampling methods and divided into experimental and control groups. Two instruments were used: The Biology Achievement Test (BAT), with a reliability coefficient of 0.97, and the Biology Students’ Interest Questionnaire (BSIQ), with a reliability coefficient of 0.82. The data were analysed using descriptive statistics and a Z-test at the significance level. Results revealed that students taught using an adaptive teaching strategy achieved significantly higher scores than those taught with the conventional method. Findings also showed that students’ interest in Biology increased after exposure to adaptive teaching strategies. Furthermore, female students exposed to adaptive teaching strategies performed significantly better than their male counterparts. The study concludes that the adaptive teaching strategy enhances academic achievement and interest in Biology but is not gender-neutral. It recommends the wider adoption of adaptive teaching strategies in biology instruction.